Influence of Intrinsic and Extrinsic Motivation in Learning Among Primary School Students - Ramalingam, Khasturi; Jiar, Yeo Kee (CENTRAL ASIA AND THE CAUCASUS, 2022)
Motivation is vital for students to face obstacles to achieving their aspirations. It determines the extent of the student’s active involvement and attitude towards learning. This concept paper aims to identify the motivation and factors that increase motivation among students in learning language. The methodology of this concept paper is based on research in the library through the collection of information and materials based on previous studies related to influencing factors and ways to increase motivation among students. Among the theories that can be linked to motivation are Gardner’s Theory of Motivation and Self-Determination Theory (SDT). Motivation is an important factor behind a person's desire to succeed or achieve a goal. Motivation can also be defined as a stimulus for achieving success or avoiding failure. Motivation is one of the important things in a student because motivation is an important element that affects student language learning. The language learning of students not only depends on the teaching and learning of the teacher but also involves the students themselves i.e. self -motivation. Motivation has two types, namely intrinsic and extrinsic motivation. Motivation that comes from within the self is intrinsic motivation, while motivation that comes from outside the self in doing something is called extrinsic motivation. Therefore, this study is very important to identify the factors that influence motivation and ways to increase motivation among students in an effort to improve student language learning.